Aristida oligantha - a new alien species on the eastern Adriatic coast - Stešević, Danijela (Array, 2021)
An alien and potentially invasive species of North American origin Aristida oligantha Michx. was found in the hinterland of Velika plaža, a sandy beach in the town of Ulcinj (Montenegro), the second known record of this plant in Europe. Here we describe the Aristida oligantha community. Further monitoring is suggested in order to evaluate its invasiveness and to plan appropriate eradication measures.